SAE Technical Paper Series 1999
DOI: 10.4271/1999-01-0509
|View full text |Cite
|
Sign up to set email alerts
|

Diesel Combustion: An Integrated View Combining Laser Diagnostics, Chemical Kinetics, And Empirical Validation

Abstract: February 1999This is a preprint of a paper intended for publication in a journal or proceedings. Since changes may be made before publication, this preprint is made available with the understanding that it will not be cited or reproduced without the permission of the author. PREPRINTThis paper was prepared for submittal to the DISCLAIMER This document was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor the University of California … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
201
0
15

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 323 publications
(226 citation statements)
references
References 45 publications
(72 reference statements)
10
201
0
15
Order By: Relevance
“…Diesel engine chemistry has been primarily an experimental subject, but the phenomenological model of Dec [15][16][17][18][19][20][21] has provided a framework within which focused computational studies can provide valuable insights. The present kinetic modeling analysis fits conveniently into Dec's framework, connecting the fuel vaporization and air entrainment processes with the soot growth period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diesel engine chemistry has been primarily an experimental subject, but the phenomenological model of Dec [15][16][17][18][19][20][21] has provided a framework within which focused computational studies can provide valuable insights. The present kinetic modeling analysis fits conveniently into Dec's framework, connecting the fuel vaporization and air entrainment processes with the soot growth period.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore these incompletely oxidized species such as CO, H 2 and small, intermediate hydrocarbon species including acetylene, ethene, propene and others then react to produce soot [17][18][19] which is later consumed in a diffusion flame environment 19 farther downstream of the ignition region. The same unsaturated hydrocarbon species have been identified as major contributors to soot production in both diesel engines and laboratory flames [21][22][23][24][25][26][27][28][29][30][31][32] .…”
Section: Modeling Approachmentioning
confidence: 99%
“…Low-temperature reactions produce an increasing amount of H 2 O 2 that is stable until its decomposition temperature is reached; since this reaction is part of the H 2 /O 2 reaction submechanism, it is independent of the specific hydrocarbon fuel being studied. Past kinetic modeling studies have demonstrated that this same decomposition reaction is responsible for the onset of knock in spark-ignition engines [21,25,26], ignition in diesel engines [26,27], and ignition under homogeneous charge compression ignition (HCCI) conditions [26,28].…”
Section: Resultsmentioning
confidence: 99%
“…[38]. Figure 16(a) presents the predicted mole fractions for some soot precursor species (C 2 H 2 , C 2 H 4 , and C 3 H 6 ) at φ = 3.0 in "air", p 5 = 50 atm, and T 5 = 770 K for both TPGME and nheptane.…”
Section: Tpgme-5=>productsmentioning
confidence: 99%